A boy with a submicroscopic 22qter deletion, general overgrowth and features suggestive of FG syndrome. - de Vries, B; Bitner-Glindzicz, M; Knight, S; Tyson, J; MacDermont, K; Flint, J; Malcolm, S; Winter, R (2000)
Over recent years, submicroscopic subtelomeric rearrangements have been shown to be a significant cause of mental retardation and, therefore, such abnormalities should be considered in every child with moderate to severe retardation with additional features suggestive of a chromosomal abnormality. The FG syndrome is an X-linked recessive mental retardation syndrome with congenital hypotonia, relative macrocephaly, a characteristic facies and constipation. We describe a severely mentally retarded boy with a history of severe constipation, truncal hypotonia, facial dysmorphism, fetal pads, and joint laxity, leading to an initial diagnosis of FG syndrome at the age of 3 years. Clinical re-evaluation at the age of 6 years, when he showed signs of general overgrowth, initiated a telomere screen, and a submicroscopic 22q13.3 telomere deletion was detected. The features suggestive of FG syndrome in this boy with a 22q13.3--> qter deletion may indicate testing for submicroscopic 22qter deletions in patients with atypical features of FG syndrome without a definite X-linked family history.